2019
DOI: 10.1002/chem.201902083
|View full text |Cite
|
Sign up to set email alerts
|

Glycine Substitution Effects on the Supramolecular Morphology and Rigidity of Cell‐Adhesive Amphiphilic Peptides

Abstract: Self‐assembling peptides that are capable of adopting β‐sheet structures can generate nanofibers that lead to hydrogel formation. Herein, to tune the supramolecular morphologies, mechanical properties, and stimuli responses of the hydrogels, we investigated glycine substitution in a β‐sheet‐forming amphiphilic peptide. Glycine substitution generally enhances conformational flexibility. Indeed, glycine substitution in an amphiphilic peptide weakened the hydrogels or even inhibited the gelation. However, unexpec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…We reported that A8G formed a hydrogel at 1.0 % (w/v) at 20°C in an acidic aqueous medium. [27] A8βAla and A8Abu bearing one and two carbon longer central alkylene chains than A8G also formed self-standing opaque hydrogels under identical conditions (Figure 1a, b). In rheological measurements using oscillatory viscometry, A8βAla in the aqueous medium showed storage modulus G' = 3.2 × 10 3 Pa and loss modulus G" = 2.9 × 10 2 Pa (Figure 2a).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We reported that A8G formed a hydrogel at 1.0 % (w/v) at 20°C in an acidic aqueous medium. [27] A8βAla and A8Abu bearing one and two carbon longer central alkylene chains than A8G also formed self-standing opaque hydrogels under identical conditions (Figure 1a, b). In rheological measurements using oscillatory viscometry, A8βAla in the aqueous medium showed storage modulus G' = 3.2 × 10 3 Pa and loss modulus G" = 2.9 × 10 2 Pa (Figure 2a).…”
Section: Resultsmentioning
confidence: 97%
“…[20,26] Recently, we reported that substitution of an alanine residue with glycine at the center of an amphiphilic peptide results in bundling of the nanofibers and enhanced mechanical properties of the hydrogel. [27] Unlike a terminal alkyl tail, internal alkylene chains with different lengths can influence not only the hydrophobicity but also the conformational flexibility and packing of the peptide molecules. Self-assembled peptide nanofibers bearing terminal alkyl tails are increasingly used as biomaterials to mimic an extracellular matrix, yet the influence of internal alkylene chains on self-assembly, nanofiber structure and biological properties remains poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…[100] MAX1I8 showed a faster gelation process than MAX1 (30 s vs 75 min to reach a G′ of 100 Pa), and formed hydrogel with a G′ as high as 1320 Pa after 2 h. However, Muraoka and coworkers showed that substitution of alanine with glycine (A8G, RADARADA(RADA) 2 ) in the middle of the RAD16 peptide ((RADA) 4 ) increased the stiffness of the hydrogel (G′ RADA16 = 265 Pa, G″ RADA16 = 42 Pa; G′ A8G = 469 Pa, G″ A8G = 56 Pa). [101] The enhanced stiffness of A8G probably resulted from the formation of twisted -sheet structures and nanofiber bundles due to a transition in the molecular packing. These results suggested that a balanced rigidity and flexibility of filament should be reached to achieve high stiffness.…”
Section: Mechanical Propertymentioning
confidence: 99%
“…As a result, cross-linked RADA-based peptide fibers form hydrogels with high mechanical strength. The mechanical strength of hydrogels can be further enhanced by replacing an alanine residue to glycine [ 56 ]. Self-assembled peptide fibers composed of β -hairpin structures with multiple hydrogen bonds by the introduction of a bend structure derived from repeated proline residues were reported by Schneider ( Figure 2 c) [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ].…”
Section: Peptide-based Self-assembliesmentioning
confidence: 99%
“…In pioneer works, amphiphilic peptides having hydrophobic alkyl chain at the termini of hydrophilic peptides have been designed, and their fundamental properties and applications to biomaterials have been investigated [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Currently, both amphiphilic peptides and other peptide-based self-assembly units have been found, enabling the design of peptide fibers with a variety of functions [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , …”
Section: Introductionmentioning
confidence: 99%